Safety aspects of de novo DCB-only PCI—a practical checklist and a simplified revised dissection classification - Corballis, Natasha H.; Merinopoulos, Ioannis; Natarajan, Rajkumar; Gunawardena, Tharusha; Wickramarachchi, Upul; Vassiliou, Vassilios S.; Colombo, Antonio; Scheller, Bruno; Eccleshall, Simon (Frontiers in Cardiovascular Medicine, 2025)
There is increasing use of drug-coated balloons (DCBs) in de novo coronary disease, supported by an ever-expanding evidence base. However, DCB-only angioplasty requires a slightly modified lesion preparation strategy to ensure an optimal angioplasty result and minimise the risk of vessel-threatening dissection. In this article, we discuss the importance of optimal lesion preparation and vessel safety based on clinical and angiographic findings, as well as the selection and deployment of appropriate DCB. We outline a new and simplified classification of dissections: those that are safe to leave untreated (type 1) and those that require modification or stenting (type 2). We also present this classification in a simple graphical format. Finally, we provide a checklist for the complete process. This review article aims to accelerate the learning curve for DCB-only percutaneous coronary intervention (PCI), highlighting the importance of lesion preparation and dissection assessment while ensuring patient safety throughout the procedure. We hope this will facilitate the adoption of safe DCB-only PCI.